Assessing Immunological Memory in the Solitary Ascidian Ciona robusta - Melillo, Daniela; Marino, Rita; Della Camera, Giacomo; Italiani, Paola; Boraschi, Diana (Frontiers in Immunology, 2019)
The immune defensive mechanisms active in the solitary ascidian Ciona robusta include phagocytic and encapsulating activity, largely brought about by phagocytic cells within the haemocyte population, the presence of complement components, which have been molecularly and functionally identified, and expression of a number of immune-related genes and pathways, identified by genome-based homology with vertebrate counterparts. Since C. robusta only displays highly conserved innate immune mechanisms, being devoid of an adaptive immune system, this organism is an excellent model for studying the features of innate memory, i.e., the capacity of the innate immune system to re-programming its responsiveness to potentially dangerous agents upon repeated exposure. In this study, we have developed an in vivo model for assessing the establishment and molecular/functional features of innate memory, by sequentially exposing C. robusta to a priming stimulus (microbial molecules), followed by a period of resting to return to basal conditions, and a challenge with microbial agents in homologous or cross-stimulation. The endpoints of immune activation were a functional activity (phagocytosis) and the molecular profiles of immune-related gene expression. The results show that exposure of C. robusta to microbial agents induces a reaction that primes animals for developing a different (expectedly more protective) response to subsequent challenges, showing the effective establishment of an immune memory. This immune memory relies on the modulation of a number of different mechanisms, some of which are priming-specific, others that are challenge-specific, and others that are non-specific, i.e., are common to all priming/challenge combinations (e.g., up-regulation of the Tnf and Lbp genes). Memory-dependent expression of the humoral immunity-related gene C3ar inversely correlates with memory-dependent variations of phagocytic rate, suggesting that complement activation and phagocytosis are alternative defensive mechanisms in C. robusta. Conversely, memory-dependent expression of the cellular immunity-related gene Cd36 directly correlates with variations of phagocytic rate, suggesting a direct involvement of this gene in the functional regulation of phagocytosis.